2016
DOI: 10.1111/den.12760
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of antithrombotic therapy may be associated with a high incidence of colonic post‐polypectomy bleeding

Abstract: The present study showed that the overall PPB rate under the new guidelines was not significantly higher when compared with the previous data obtained before the new guidelines were introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Consistent with this finding, the use of anticoagulants or antiplatelet agents is considered to promote POB in patients treated with EP or EMR [18][19][20] . Thus, the use of anticoagulants or antiplatelet agents increases the risk of POB following EMR, EP, and ESD.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Consistent with this finding, the use of anticoagulants or antiplatelet agents is considered to promote POB in patients treated with EP or EMR [18][19][20] . Thus, the use of anticoagulants or antiplatelet agents increases the risk of POB following EMR, EP, and ESD.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies showed that multiple factors such as size, pedunculated form, and proximal location increase the rate of POB following EP [19,25,26] . In addition, antithrombotic therapy, hypertension, chronic renal disease, cardiovascular disease, and advanced age were identified as patient-associated risk factors for delayed bleeding [18][19][20] . Based on these previous reports, we performed a univariate analysis of the clinical parameters in this retrospective study.…”
Section: Risk Factors For Pob Following Colorectal Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the antithrombotic agents, HB therapy has been reported to be a strong risk factor for PPB [7,15,30,31]. Ishigami et al [31] reported that the OR of PPB in patients treated with HB was 9.8 compared with that of patients without antithrombotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PPB risks associated with each type of antithrombotic, such as aspirin, thenopyridine, warfarin, or heparin, have been reported [7,[9][10][11][12][13][14][15], and several guidelines have been published regarding possible management modalities [16][17][18][19][20][21]. In contrast, the number of patients treated with multiple antithrombotics, such as dual antiplatelet therapy, is also increasing [22,23], but little is known about the PPB risk in patients receiving multiple antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%